Study about Developmentally Appropriate Practice and Music Education in the Primary School - Benjamin Adjepong (Current Research in Language, Literature and Education Vol. 2, 2021)
Developmentally Appropriate Practice (DAP) is an educational approach which refers to teaching strategies that consider children’s age, interests, abilities and experiences to help them to achieve challenging and achievable goals. The approach which hinges on three pillars: age, individual and culture has gained popularity in countries such as the United States of America, Taiwan and South Korea. DAP underpins the National Association for Music Education (NAfME) beliefs about young children’s developmentally and individually appropriate musical experiences. The aim of this paper is to present an overview of the relationship between DAP and music education in primary schools. It is intended to provide teachers with adequate knowledge and understanding of DAP as an educational concept and its application in the music classroom. The discussions centred around the following themes: Children’s musical potential, children’s unique interests and abilities, children’s play, an exemplary musical sound, activities and material, performance goals, diverse learning environment, effective adult role models, and a pleasant physical and social environment. It is suggested that training workshops should be organised for teachers for effective integration of DAP in the classroom to optimise children’s learning in music. Inclusion of DAP as a theme for study in the music curriculum content in the Universities and Colleges of Education in Ghana for the preparation of primary school teachers is also recommended. Carrying out a real classroom study through observations, questionnaires or interviews is recommended for future researches on related subjects.